Nonlinear analysis of quadrilateral composite plates using moving kriging based element free Galerkin method. (1st January 2017) - Watts, Gaurav; Pradyumna, S.; Singha, M.K.
Abstract: Element free Galerkin (EFG) method with moving kriging (MK) shape functions is employed here to investigate geometrically nonlinear bending behavior of shear deformable isotropic and laminated composite straight-sided quadrilateral plates. Nonlinear governing equations derived based on the first order shear deformation theory and von Karman strains are solved using Newton-Raphson iterative technique. The applicability and accuracy of the EFG method for the linear and nonlinear bending analyses of isotropic arbitrary quadrilateral plates are examined. Thereafter, geometrically nonlinear analyses of trapezoidal and arbitrary straight-sided quadrilateral thin and moderately thick composite plates are presented for the first time, which may serve as benchmark results for future research purposes.